Bromodomain-Containing Protein BRD4 Is Hyperphosphorylated in Mitosis - Wang, Ranran (Cancers (Basel), 2020)
The epigenetic reader BRD4 binds acetylated histones and plays a central role in controlling cellular gene transcription and proliferation. Dysregulation of BRD4′s activity has been implicated in the pathogenesis of a wide variety of cancers. While blocking BRD4 interaction with acetylated histones using BET inhibitors (BETis) has been tested in clinical trials, many cancers have acquired BETi resistance. However, the underlying mechanisms are poorly understood and BETi resistance remains a pressing clinical problem. We previously showed that BRD4 phosphorylation supports stronger chromatin binding and target oncogene expression. In this study, we discovered that BRD4 is hyperphosphorylated by CDK1 during mitosis and determined the major CDK1 phosphorylation sites in BRD4. Using CRISPR/Cas9 gene editing, we replaced endogenous BRD4 with a non-phosphorylatable mutant and demonstrated that CDK1-mediated BRD4 phosphorylation contributes to BETi resistance. CDK1 over-activation frequently observed in cancers has the potential to cause aberrant BRD4 hyperphosphorylation persisting outside of mitosis to strengthen its target gene binding and confer BETi resistance. We found that dual CDK1 and BET inhibition generates a synergistic effect in killing BETi-resistant cancer cells. Our study therefore suggests that CDK1 inhibition can be employed to overcome tumor BETi resistance and improve treatments for BRD4-associated cancers.